2008
DOI: 10.1016/j.jmb.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Cytosine Deaminase Mutants with Increased Thermostability Impart Sensitivity to 5-Fluorocytosine

Abstract: SUMMARYProdrug gene therapy (PGT) is a treatment strategy in which tumor cells are transfected with a 'suicide' gene that encodes a metabolic enzyme capable of converting a nontoxic prodrug into a potent cytotoxin. One of the most promising PGT enzymes is cytosine deaminase (CD), a microbial salvage enzyme that converts cytosine to uracil. CD also converts 5-fluorocytosine (5FC) to 5-fluorouracil (5FU), an inhibitor of DNA synthesis and RNA function. Over 150 studies of cytosine deaminasemediated PGT applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 42 publications
3
45
0
Order By: Relevance
“…Parenthetically, the Kd for 5-FC of the yCD protein used in this study has been measured as 18 mg/ ml (140 mM). 34 Consequently, all the 5-FC concentrations used here are well below this Kd. In agreement with the Kd, we have shown that yields of 5-FU continue to increase with increasing 5-FC up to 5.0 mg/ml (38.7 mM) in assays performed using infected U-87 cell extracts (Supplementary Fig.…”
Section: Expression Of the CD Protein Is Necessary To Sensitize Toca mentioning
confidence: 79%
See 1 more Smart Citation
“…Parenthetically, the Kd for 5-FC of the yCD protein used in this study has been measured as 18 mg/ ml (140 mM). 34 Consequently, all the 5-FC concentrations used here are well below this Kd. In agreement with the Kd, we have shown that yields of 5-FU continue to increase with increasing 5-FC up to 5.0 mg/ml (38.7 mM) in assays performed using infected U-87 cell extracts (Supplementary Fig.…”
Section: Expression Of the CD Protein Is Necessary To Sensitize Toca mentioning
confidence: 79%
“…CD-based cancer gene therapy has proven to be effective in chemotherapyresistant cancer cell lines, 31,32 in combination with chemotherapy, 4 and to enhance the effect of radiotherapy. 33 To further improve the wild-type CD, we developed a codon-optimized, 7 heat-stabilized 34 yeast CD (yCD) gene, which resulted in an approximate 3-fold greater enzyme-specific activity compared with the wild-type protein when incorporated into Toca 511.…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations of the yCD/5FC system is the thermolabile nature of yCD at 37 C. To overcome this problem, two enzyme mutants (yCDdouble and yCDtriple) with increased half-lives and melting temperatures were identified that significantly increased the sensitivity of cancer cells to 5FC treatment compared with wild-type yCD [50,51]. Leveille et al showed the benefits of optimizing each step in a multicomponent therapy for efficient clinical outcome [52].…”
Section: Cytosine Deaminase/5-fluorocytosine Systemmentioning
confidence: 99%
“…The CD/5-FC system demonstrates stronger bystander effect and the gap-junctional intercellular communications than other suicide gene system, which results in strong inhibition of tumor growth (Khatri et al, 2006;Stolworty et al, 2008;Dachs et al, 2009). However, there is no efficient method to deliver the CD gene into the tumor target cells, which hampers the application of the suicide gene therapy.…”
Section: Introductionmentioning
confidence: 99%